An Insight into the Traditional Uses, Phytochemicals, and Pharmacological Properties of Polyalthia bullata King - Giwa, Hadiza Shehu; Hamid, Hazrulrizawati Abd (Current Traditional Medicine, 2025)
Polyalthia bullata King or Tongkat Ali Hitam, a term in the Malay language, encompasses a diverse group of plants belonging to different genera of the Annonaceae family. The native range of this species is Myanmar to Peninsula Malaysia, Borneo. It is a shrub or tree and grows primarily in the wet tropical biome. These plants have been utilized in Malaysia and Southeast Asia as an herbal aphrodisiac. The extracts of this plant have been reported to exert pharmacological activities, such as antioxidant, cytotoxicity, and aphrodisiac properties. The therapeutic properties of P. bullata are attributed to the presence of alkaloids and flavonoids. This study thoroughly analyzes the phytochemical and pharmacological research on P. bullata and its traditional medicinal properties. The review aims to provide a critical update on the scientific knowledge of P. bullata and to identify novel possibilities for investigating its therapeutic potential. There is limited scientific research on the phytochemical components and pharmaceutical application of P. bullata. To date, only a few compounds have been identified and isolated. There is a need for future studies to focus on the extraction technology, phytochemical profiling, and isolation of bioactive compounds from P. bullata to fill the research gap as well as to provide an important theoretical basis and valuable references for researchers and pave the way for the discovery and development of new and existing drugs.
Keywords: Polyalthia bullata King